A novel optimization-based power quality enhancement using dynamic voltage restorer and distribution static compensator - Madduluri Chiranjivi; Katragadda Swarnasri (Institute of Advanced Engineering and Science, 2022)
The power assurance for distinct purchaser in the nation must be guaranteed through electric power distribution (EPD) system, subsequently EPD must be reliable, and well facilitating with power quality (PQ) in distribution framework. It will be much significant to keep up with PQ in power distribution (PD) framework for service continuity. The PQ issue basically emerge in distribution framework are voltage swell, sag, harmonics, and disparities in power. In this manuscript, the PQ development in photovoltaic (PV) PD framework for IEEE 33 and 57 bus frameworks is deliberated as the aim. The improvement is satisfied with FACTS pay gadgets of dynamic voltage restorer (DVR) and distributed static compensator (DSTATCOM). The butterfly optimizer (BO) and gray wolf optimizer (GWO) framework is deliberated for suggested work that implies a switching gadget and it compares the yield signal of DSTATCOM and DVR. In this proposed system DVR is compensated with an advanced GWO and DSTATCOM with BO for optimal location of FACTS devices in IEEE 33 and 57 bus systems are discussed like in the conventional paper as 13th bus for IEEE 33 system & 30th bus for IEEE 57 system.